2004
DOI: 10.1128/aac.48.10.3677-3683.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ketolide Antimicrobial Activity Persists after Disruption of Interactions with Domain II of 23S rRNA

Abstract: Ketolides are the latest derivatives developed from the macrolide erythromycin to improve antimicrobial activity. All macrolides and ketolides bind to the 50S ribosomal subunit, where they come into contact with adenosine 2058 (A2058) within domain V of the 23S rRNA and block protein synthesis. An additional interaction at nucleotide A752 in the rRNA domain II is made via the synthetic carbamate-alkyl-aryl substituent in the ketolides HMR3647 (telithromycin) and HMR3004, and this interaction contributes to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
1
22
0
1
Order By: Relevance
“…However, the conclusions about the contribution of the 11,12 side chain to the drug activity should be drawn only cautiously. Although original studies suggested that interactions of the side chain of ketolides with A752 in the loop of helix 35 in 23S rRNA significantly contribute to the drugs' affinity (9,17,49), more recent genetic studies questioned that conclusion because mutations at and around A752 or at U2609, with which the side chains interact, had only a minor effect upon drug inhibitory action (14,21,30,49). In agreement with these observations, the additional interaction afforded by the extended side chains of telithromycin and CEM-101 or, for that matter, the fluorine atom at the C-2 position of the CEM-101 lactone did not translate in our study to an improved ability of either of the ketolides compared with that of azithromycin in inhibiting erythromycin binding to the ribosome (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, the conclusions about the contribution of the 11,12 side chain to the drug activity should be drawn only cautiously. Although original studies suggested that interactions of the side chain of ketolides with A752 in the loop of helix 35 in 23S rRNA significantly contribute to the drugs' affinity (9,17,49), more recent genetic studies questioned that conclusion because mutations at and around A752 or at U2609, with which the side chains interact, had only a minor effect upon drug inhibitory action (14,21,30,49). In agreement with these observations, the additional interaction afforded by the extended side chains of telithromycin and CEM-101 or, for that matter, the fluorine atom at the C-2 position of the CEM-101 lactone did not translate in our study to an improved ability of either of the ketolides compared with that of azithromycin in inhibiting erythromycin binding to the ribosome (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the role of position G745 in the tylosin-ribosome interactions in E. coli has been described (Liu & Douthwaite, 2002b), while positions G748 and A752 are reportedly involved in the interactions between ketolides and ribosomes (Novotny et al, 2004). Additionally, both L4 and L22 proteins are implicated in this ribosome-macrolide interaction (Chittum & Champney, 1994;Gabashvili et al, 2001).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Alterations present in domain II of the 23S rRNA affect specific macrolides like tylosin and ketolide antibiotics but not erythromycin or azithromycin. Thus, amino acid changes, deletions or insertions at position A752 result in low levels of telithromycin resistance (Novotny et al, 2004). Curiously, the concomitant presence of any A752 alteration in combination with the presence of A2058G results in the loss of telithromycin resistance but with an increase in tylosin resistance (Novotny et al, 2004).…”
Section: S Rrna Base Substitutionsmentioning
confidence: 99%
See 2 more Smart Citations